The Influence of Work Life Balance and Burnout on Job Satisfaction Among Civil Servants at the Gang Sehat Community Health Center in Pontianak City - Saputra, Riski Alfiandi; Arninda, Arninda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to explore the influence of Work-Life Balance and Burnout on Job Satisfaction among Civil Servants (PNS) at the UPT Puskesmas Gang Sehat, Pontianak City. Using a quantitative approach and associative method, data was collected through the distribution of questionnaires to 38 civil servants at the health center, along with in-depth interviews with the Head of Administration. Multiple linear regression analysis showed that Work-Life Balance has a significant positive effect on Job Satisfaction. This indicates that the better the balance between work and personal life, the higher the level of job satisfaction among employees. Conversely, Burnout showed a non-significant negative effect on Job Satisfaction. The results of the simultaneous test (F-test) indicated that both variables, Work-Life Balance and Burnout, simultaneously have a significant effect on Job Satisfaction. These findings emphasize the importance of attention to work-life balance among employees, which has been shown to enhance job satisfaction. Meanwhile, Burnout, although it affects performance, does not significantly contribute to job satisfaction in the context of this study. This research provides insights for Puskesmas management to consider implementing policies that support work-life balance among employees as part of efforts to improve job satisfaction and productivity.